ANALISIS SINTAKSIS KALIMAT TUNGGAL DALAM TEKS BIOGRAFI BJ HABIBIE PADA MEDIA DARING SCRIBD.COM - Siti Azizah; Natasya Marthasifa; Rista Septiwiyanti; Mya Mulyany (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze simple sentences in the biography text of BJ Habibie on the online platform Scribd.com. The focus of the research is to identify the patterns of simple sentence usage found in the biography. A descriptive qualitative method was employed, with data collected through literature review. The findings show that the simple sentences in the biography text are dominated by basic structures consisting of a single subject and predicate, occasionally accompanied by objects, complements, or adverbials. These sentences are used to convey essential information directly, such as personal background, education, and contributions of the figure. The most common sentence patterns found are S-P and S-P-O. The effective use of simple sentences in the biography facilitates readers in understanding the information clearly and concisely.